Trafficking Captives in South America’S Southern Cone the Continental Route from Rio de la Plata to Lima in the Late Colonial Period - Martinez-Barraza, J (Brill Academic Publishers, 2024)
This article demonstrates the logic, efficacy and profitability of the commerce in enslaved persons between Rio de la Plata and Lima from the late 1760s to the second decade of the nineteenth century. Moving beyond the customary study of local markets, it combines newly located tax, custom and notarial records with recent studies to describe the intercontinental slave trade in the Southern Cone. It demonstrates how Lima’s demand for labor lay behind the transportation of more than 25,000 enslaved persons over the pampas and across the Andes to the port of Valparaiso, for final delivery in Lima’s port of Callao. We find that most of the trafficking was concentrated in the summer and fall, consisted of the transportation of fewer than four slaves at a time, and was undertaken by hundreds of actors playing a variety of commercial roles. © 2024 Brill Academic Publishers. All rights reserved.
Keywords: slavery; late colonial Southern Cone; commerce; Spanish Empire; slave trafficking